Physico-Mechanical Foundations and Optimization of Centrifugation Regimes in Beeswax Rendering (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The article examines the process of beeswax rendering in an innovative centrifugal unit with steam heating as a complex multistage heat and mass transfer and mechanical system. Unlike traditional wax rendering methods, the proposed approach implements forced mechanical intensification of the process through the action of centrifugal forces, which significantly alters the energy structure of phase separation and increases the efficiency of wax extraction from the porous structure of comb residues.The process is described from the standpoint of thermodynamics of open systems, taking into account internal entropy production, phase transition phenomena, and viscous filtration of molten wax. A physico-mechanical model is proposed that combines heat conduction, a Stefan-type melting problem for beeswax, and a generalized Darcy–Forchheimer law with an additional centrifugal driving pressure. Quantitative analysis of the influence of operating parameters is performed using a second-order multifactor regression model with the construction of response surfaces.It is established that the dominant factors determining beeswax yield are the rotational speed of the centrifuge drum and the duration of the process, whereas steam temperature has an auxiliary character and should be limited from the standpoint of energy efficiency. Based on the analysis of local sensitivities and response surfaces, rational centrifugation regimes are identified, ensuring an increase in wax yield of up to 90% while reducing specific energy consumption by approximately 20% compared with traditional methods. The obtained results can be used in the design and optimization of industrial units for beeswax rendering.
Keywords: beeswax; centrifugation; heat and mass transfer; phase transition; multifactor optimization; response surfaces; energy efficiency